PENERJEMAHAN SLANG (PRANCIS-INDONESIA) PADA TAKARIR SERIAL FILM LUPIN SERI 1 (EPISODE 1—5) - Gitamorezqi Maharani; Diana Rosita; Setia Rini (Universitas Hasanuddin, 2024)
The objectives of this research are: to identify the types and meanings of slangs in a serial film, Lupin, season 1; to describe the strategies used in their translation in Indonesian; and to describe the implication in learning French. This research uses a qualitative descriptive method, with the observation method to collect data and the identification method to analyze the data. According to the result, there are 546 data of 73 primary slangs and 473 secondary slangs. One slang can consist of one or more meanings, depending on the type of slang and the context of the speech. As for the slang translation strategy, the most used is transfer, then paraphrase, deletion, dislocation, condensation, decimation and expansion. While the imitation, transcription and resignation are not found. In learning French, this result allows learners to enrich their knowledge of slang and the strategy for translating it.